The early generation of Yanggongju (Western Princess) and their life polemics in 1950-1955 - Ashanti Widyana; Fina Fianita; Jayanti Megasari (Journal of Korean Applied Linguistics, 2021)
Yanggongju, the sexual workers for G.I. soldiers who were stationed in Korea particularly during and after Korean war, were stigmatized as 'bad women' for having sexual relationships out of marriage with foreign men. These women must endure hardships that came from the clients or the pimps in daily basis. This study aims to investigate how the life and polemics yanggongju had experienced in the period of 1950-1955. The early generations of yanggongju consisted of women with various backgrounds, such as war widows and women who became the breadwinner of the family. This study used qualitative method and the data were collected from the articles of Kyunghyang Shinmun, Dong-a Ilbo, and Chosun Ilbo in the period of January 1, 1950, to December 31, 1555, accessed from a news archive site called naver news library.  After two-times process of data reduction, 47 articles were collected under the category of nyu-seu (news). It was found that the early generation of yanggongju experienced at least four kinds of polemics in their life: (1) life difficulties (physically and mentally), such as fallen women stigma, vulnerable to sexual transmitting disease, and having many debts, (2) child neglect in the form of attempted abortion and child abandonment, (3) suicide and abused, and (4) alcohol and drug (opium) addiction. It is hoped that this research can contribute to further researches on the problem of yanggongju and their position as a marginalized people.